The Italian Information System on Zoonoses Data Collection. (4th June 2012) - Colangeli, P.; Iannetti, S.; Ruocco, L.; Forlizzi, L.; Cioci, D.; Calistri, P.
Summary In the framework of the international obligations subscribed by the Italian government, the Italian Ministry of Health should provide the European Union (EU) (European Commission, European Food Safety Authority – EFSA) with a set of data and information related to the report and the spread of zoonoses and to the activities put in place for monitoring and control of zoonoses. In 2008, the Italian Ministry of Health commissioned the Istituto G. Caporale (ICT) to implement an information system able to provide information and data on the monitoring and control of zoonoses in the national territory, in accordance with the national and community legislation. The system is part of the e‐Government process that involves all public administrations of the EU and refers to the use of information and communication technologies for the digital processing of documents in order to obtain simplification and interoperability of administrative procedures through the Internet, as defined in the strategic lines published by the National Centre for Information Systems in Public Administration (DigitPA) in 2009–2011.